Literature Review: Emotional Regulation and Toxic Relationships in Late Adolescents - Petra Johanna; Winida Marpaung; Rina Mirza; Beby Astri Tarigan; Mukhairah El Akmal (Psikologi Prima, 2025)
The phenomenon of toxic relationships has recently come under public scrutiny due to its widespread prevalence. This issue typically focuses on middle and late adulthood or parenting. This study examines the importance of emotional regulation and toxic relationships in late adolescence through a literature review. A literature review examines theories through the depth and breadth of previous research, including reviews of published journals and books. In general, it was found that the phenomenon of toxic relationships has pervaded late adolescence, and its relationship with emotional regulation is significantly negative. This means that if an individual has good or high emotional regulation, a toxic relationship will not occur. Conversely, if their emotional regulation is poor or low, a toxic relationship will occur.